The Analysis Study of Impact of Health Promotion Lifestyle Inteventions for Weight Management in Psychosis : A Comprehensive Systematic Review - Butar Butar, Ruth Natalia; Franky Cornelius Butar Butar, Franky Cornelius Butar Butar; Butar Butar, Devi Anggraeni Novalinda (The Indonesian Journal of General Medicine, 2024)
Background: The impact of lifestyle interventions on individuals with psychotic disorders is complex and multifaceted. These interventions, including smoking cessation, increased physical activity, and healthy dietary practices, can help reduce obesity and cardiovascular disease risk factors. Therefore, understanding the relationship between health promotion in lifestyle interventions and psychiatric disorders is crucial for developing effective treatment regimens. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2011 and 2024. Result: The study looked at more than 20000 publications using reputable sources including Science Direct, SagePub, and PubMed. After it was decided that eight publications needed greater investigation, a more extensive review of the entire literature was carried out. Conclusion: The study evaluated the effectiveness of a lifestyle intervention in psychotic patients, focusing on health behaviors like physical activity and nutritious food consumption. Although the intervention increased physical activity, it did not significantly enhance clinical outcomes, suggesting the intervention period may not be sufficient.